Public Response to Education and Prevention Efforts of Covid-19 in Instagram @satgascovididijatim - Trisna, Indri Wachidah Wahyuni; Rosyidah, Hariri Ulfa'i; Huda, Sokhi (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2020)
This study aims to determine the public's response to education and prevention of COVID-19 on Instagram social media @satgascovididijatim and to find out the effectiveness of Instagram social media as a medium to convey information to the public. This study uses a descriptive qualitative approach with a phenomenological analysis perspective. Research data obtained by the methods of observation, interviews, and documentation. There are two points from this research. First, the Indonesian Doctors Association (IDI) of East Java Province educates and prevents COVID-19 through the @satgascovididijatim Instagram account to the public, especially the people of East Java, to prevent the spread of the Corona virus. Second, the community provides three forms of response; cognitive, affective, and behavioral. The response stated that the Instagram account @satgascovididijatim is one of the effective media in delivering educational messages and preventing COVID-19 to the public via Instagram social media.